SOCIAL INTERACTION IN BILINGUAL CHILDREN'S STORYBOOKS OF RIAU PROVINCE: A STUDY OF LITERARY SOCIOLOGY - Seniadi; Roziah (SOSIOEDUKASI, 2026)
This study aims to describe and analyze the representation of children's social interactions in three main environments—family, school, and community—contained in ten bilingual children's storybooks based on local Malay culture in Riau Province. The research uses a qualitative approach with a descriptive type of research. Data in the form of language units in the form of dialogues, narratives, and actions of characters that represent children's social interactions. Data collection techniques are carried out through documentation studies with reading and recording techniques, while data analysis is carried out through reduction, classification, interpretation, and drawing conclusions contextually from the perspective of literary sociology.Based on the results of a study on ten children's storybooks based on Malay local culture, it can be concluded that the most dominant representation of children's social interaction takes place in the community environment (26 data), followed by the family environment (17 data), while the school setting is not explicitly found (0 data). Quantitatively, the forms of social interaction found included: cooperation (9 data) as the most dominant pattern, accommodation (4 data), competition (1 data), and opposition (4 data), while assimilation (0 data) and contravention (0 data) were not found explicitly. The dominance of cooperation shows the strong value of mutual cooperation, solidarity, and collective responsibility in Malay culture. Accommodation serves as an educational conflict resolution mechanism, while competition and conflict are present in a limited degree and always end with reconciliation or moral learning. Thus, the social interactions in these books represent an integrative and normative social structure. Conflict is not directed at social disorganization, but rather as a means of internalizing character values such as responsibility, discipline, care, and ecological awareness. This representation emphasizes that character education in children's literature based on Riau Malay local culture is built through harmonious social dynamics, deliberation, and togetherness Based on this, it is suggested that the development of children's literature based on local culture still maintains the strength of the representation of collectivity and deliberation values, but begins to present school spaces in a more proportional manner as part of the character education ecosystem.